5th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings - Marina Bajić; Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka (2023)
The 5th International Conference on Technologies & Business Models for Circular Economy (TBMCE) was organized by the Faculty of Chemistry and Chemical Engineering, University of Maribor in cooperation with the Chamber of Commerce and Industry of Štajerska and SRIP- Circular Economy. The conference was held in Portorož, Slovenia, at the Grand Hotel Portorož from September 12th to September 14th, 2022. TBMCE 2022 was devoted to presentations of circular economy concepts, technologies and methodologies that contribute to the shift of business entities and society as a whole to a more responsible, circular management of resources. The conference program included a round table: Asia – factory of the world, what about the EU?, 4 panel discussions, 1 plenary and 4 keynote lectures, oral and poster presentations on the following topics: Sustainable energy, Biomass and alternative raw materials, Circular business models, Secondary raw materials and functional materials, ICT in Circular Economy, Processes and technologies. The event was under the honorary patronage of Mr. Matjaž Han, Minister of Economic Development and Technology.
Keywords: circular economy; sustainable development; processes and technologies; circular business models; and development